FAKTOR-FAKTOR PENGHAMBAT MENINGKATNYA KEMAMPUAN PUBLIKASI DI PROGRAM STUDI PSIKOLOGI UIN SUNAN KALIJAGA YOGYAKARTA - Very Julianto (Jurnal Psikologi Integratif, 2018)
Lecturers and students are the main actors in higher education who are tasked with implementing the Tri Dharma of Higher Education namely education / teaching, research, and community service (Law No. 12 of 2012, Article 1 Paragraph 9). The fact that is happening now, lecturers and students are still having difficulties in implementing the Tri Dharma, especially in research. One proof that shows the low publication in Indonesia is the Scimago Journal and Country Rank (2015) data which placed Indonesia in the 49th place in the world and 11th in Asia in 2015. Therefore, this study aims to determine what factors include the limited costs become an obstacle in improving the publication capacity of the Psychology study program at Sunan Kalijaga State Islamic University in Yogyakarta. The researcher used a qualitative method namely semi-structured interviews. The subjects of this study were 20 people consisting of lecturers and Psychology students at Sunan Kalijaga State Islamic University. The results of this study indicate that there are many obstacles and obstacles in publicizing the psychology study program of Sunan Kalijaga State Islamic University. These constraints lead to the lack of understanding of the research subject to the use of technology for publication.  Dosen dan mahasiswa merupakan pelaku utama di perguruantinggi yang bertugas melaksanakan  Tri Dharma Perguruan Tinggi  yaitu pendidikan/pengajaran, penelitian, dan pengabdian masyarakat (UU No. 12 Tahun 2012, Pasal 1 Ayat 9). Kenyataan yang terjadi saat ini, dosen dan mahasiswa masih kesulitan dalam melaksanakan tri dharma tersebut, terutama pada penelitian. Salah satu bukti yang menunjukkan rendahnya publikasi di Indonesia adalah data Scimago Journal and Country Rank (2015) yang menempatkan Indonesia pada peringkat 49 di dunia dan 11 di Asia pada tahun 2015. Oleh sebab itu, penelitian ini bertujuan untuk mengetahui faktor apa selaian keterbatasan biaya yang menjadi penghambat dalam meningkatkan kemampuan publikasi di prodi Psikologi UIN Sunan Kalijaga Yogyakarta. Peneliti menggunakan metode kualitatif yakni dengan wawancara semi terstruktur. Subjek penelitian ini berjumlah 20 orang yang terdiri dari dosen dan mahasiswa Psikologi UIN Sunan Kalijaga. Hasil penelitian ini menunjukkan bahwa ada banyakkendala dan hambatan dalam melakukan publikasi di prodi psikologi UIN Sunan Kalijaga. Kendala tersebut bermuara dari ketidakpahaman subjek penelitian terhadap pemanfaatan teknologi untuk melakukan publikasi.